COMBINED TELMISARTAN / HYDROCHLORTHIAZIDE THERAPY OF THE PATIENTS WITH ESSENTIAL HYPERTENSION AND ASSOCIATED ATHEROSCLEROSIS OF THE LOWER EXTREMITIES’ MAIN ARTERIES - Yarema, Nadiya; Bilochytska, Viktoriya (European Scientific Journal, ESJ, 2014)
Telmisartan/hydrochlorothiazide combined antihypertensive effect on 96 patients with arterial hypertension and associated atherosclerosis has been studied. Telmisartan has been found to reduce arterial pressure gradually, alongside with maintaining stable daily indices and improving both central and peripheral hemodynamics.